Resistance to bhendi yellow vein mosaic disease: A review - SANWAL, S K; VENKATARAVANAPPA, V; SINGH, B (The Indian Journal of Agricultural Sciences, 2016)
Yellow vein mosaic disease (YVMD), which is caused by association of many distinctive mono and bipartite begomoviruses and their satellites is the most devastating disease of okra [Abelmoschus esculentus (L.) Moench] affecting both pod yield and quality. Since it is very difficult to control the disease properly by chemical means, the only practical remedy of this problem is to develop tolerant/resistant varieties. A lot of work has been done to determine the inheritance of resistance to YVMV in okra and to identify different sources of resistance. For better utilization and improvement of current okra genetic resources, there is a need to understand and appreciate the studies related to resistance source in wild and cultivated species, associated viruses, virus-vector relationship, hot-spots for virus, favourable conditions for disease development, screening methods and breeding strategies. In this review, efforts were made to elucidate the genetics of resistance to YVMV in okra and also to provide complete information regarding sources of resistance.